Staging disorder - Stewart, Christopher 1966-; Teichmann, Esther 1980- (Black Dog Publishing, 2015)
The concept of ‘staging disorder’ looks not to how photographers have staged disordered reality themselves, but rather to how these artists have recognised and responded to a phenomenon of staging that already exists in the world. Military simulations of rooms, houses, planes, streets and whole fake towns in different parts of the globe provoke a series of questions concerning the nature of truth as it manifests itself in current photographic practice, drawing from Adam Broomberg & Oliver Chanarin’s Chicago, 2007; Claudio Hils’ Red Land Blue Land, 2000; Richard Mosse’s Airside, 2007; Sarah Pickering’s Public Order, 2002–2005; Christopher Stewarts’ Kill House, 2005 and work by An-My Lê and Geissler/Sann. In highlighting the resonance that these five projects have with one another, the publication develops a thesis on contemporary photography at a point when we are currently witnessing a shift away from a critical discourse that has been preoccupied by theoretical concerns related to artifice and illusion. Staging Disorder sits alongside an exhibition and symposium curated by Christopher Stewart (Associate Professor in Photography, Faculty of Design, Architecture and Built Environment, University of Technology Sydney) and Dr Esther Teichmann (Senior Lecturer in Photography, LCC, UAL). The exhibition will be held in the galleries of the London College of Communication and will run from 26 January-12 March, with a symposium taking place in late January.